2005
DOI: 10.1677/jme.1.01812
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinomic profile of neurointermediate lobe pituitary prohormone processing in PC1/3- and PC2-Null mice using SELDI-TOF mass spectrometry

Abstract: Pro-vasopressin and pro-oxytocin are prohormones processed in the neurointermediate lobe pituitary to form the biologically active peptide hormones, arginine vasopressin (AVP) and oxytocin. Neurointermediate lobe pituitaries from normal (+/+), heterozygous (+/−), PC2-Null (−/−), PC1/3-Null and oxytocin-Null mice were analyzed by SELDI-TOF mass spectroscopy for the peptide hormone products, AVP, oxytocin and neurophysin I and II. Molecular ion species with masses characteristic of oxytocin, AVP, neurophysin I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Comparative proteomics of the pituitary and hypothalamic extracts from WT and PCSK2-deficient mice have shown that several precursors to these peptides are either unprocessed or aberrantly processed. 11,28 The fact that the mutant mice show normal food intake despite impaired production of orexigenic peptides suggests that a balance between orexigenic and anorexigenic peptides may have been maintained. In this study, we measured the levels of the orexigenic gastric hormone ghrelin: they were comparable between WT and PCSK2-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative proteomics of the pituitary and hypothalamic extracts from WT and PCSK2-deficient mice have shown that several precursors to these peptides are either unprocessed or aberrantly processed. 11,28 The fact that the mutant mice show normal food intake despite impaired production of orexigenic peptides suggests that a balance between orexigenic and anorexigenic peptides may have been maintained. In this study, we measured the levels of the orexigenic gastric hormone ghrelin: they were comparable between WT and PCSK2-null mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this well‐studied mouse model, selective roles of PC2 in determining the production of neuropeptide Y, somatostatin‐28, enkephalin, vaso‐active intestinal polypeptide (VIP), galanin and corticotropin releasing factor (CRF) were also demonstrated by RIA (Miller et al . 2003) and, recently, the first mass spectrometry‐based study of PC2‐null mice was performed, using a surface enhanced laser desorption ionization – time of flight (SELDI‐TOF) instrument (Hardiman et al . 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1998; Allen et al . 2001), and provasopressin‐derived peptides showed no apparent change in level in PC2 KO mice tissue (Hardiman et al . 2005).…”
Section: Discussionmentioning
confidence: 99%